CLASSIFICATION BASED ON DECISION SPACES - V. V. Krasnoproshin; V. R. Rodchanka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
It's proposed a classification method based on the analysis of the feature subspaces properties. A procedure of automatic space identification where classes do not intersect is described. It's presented a possibility to use these spaces for automatic construction of classifiers.